2017
DOI: 10.1101/201996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence, Structure and Context Preferences of Human RNA Binding Proteins

Abstract: Production of functional cellular RNAs involves multiple processing and regulatory steps principally mediated by RNA binding proteins (RBPs). Here we present the affinity landscapes of 78 human RBPs using an unbiased assay that determines the sequence, structure, and context preferences of an RBP in vitro from deep sequencing of bound RNAs. Analyses of these data revealed several interesting patterns, including unexpectedly low diversity of RNA motifs, implying frequent convergent evolution of binding specific… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
283
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(311 citation statements)
references
References 86 publications
24
283
1
Order By: Relevance
“…Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA‐binding proteins, then acts as an oncogene or a suppressor oncogene . In this study, we found that knockdown of MAPKAPK5‐AS1 in CRC cells could lead to changes in related downstream genes, including p15 , p21 , p27 , p57 , KLF2 , and Trail .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA‐binding proteins, then acts as an oncogene or a suppressor oncogene . In this study, we found that knockdown of MAPKAPK5‐AS1 in CRC cells could lead to changes in related downstream genes, including p15 , p21 , p27 , p57 , KLF2 , and Trail .…”
Section: Discussionmentioning
confidence: 64%
“…In this study, we analyzed 2 sources Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA-binding proteins, [27][28][29][30] then acts as an oncogene or a suppressor oncogene. [31][32][33][34][35] In this study, we found that knockdown of MAPKAPK5-AS1 in CRC cells could lead to changes in related downstream genes, including p15, p21, p27, p57, KLF2, and Trail. Among them, p21 has high basal expression abundance in CRC cells, which aroused our interest.…”
Section: Discussionmentioning
confidence: 66%
“…Given our findings that FMRP localization targets were enriched for G-quadruplex sequences, we next sought to determine if FMRP directly interacted with G-quadruplex RNAs over other RNAs in vitro. To this end, we performed RNA Bind-n-Seq (RBNS), a quantitative and unbiased method that defines the specificity of a given RBP or RNA binding domain by incubating purified protein with a diverse pool of billions of random RNA sequences (Dominguez et al, 2018;Lambert et al, 2014;Taliaferro et al, 2016b). In this technique, the input RNA pool and proteinassociated RNA are sequenced using highthroughput sequencing.…”
Section: The Rgg Domain Of Fmrp Specifically Recognizes G-quadruplex mentioning
confidence: 99%
“…The RNA Bind-n-Seq assay was performed similar to previously described (Dominguez et al, 2018). Briefly, RNA with a random region of 40nt was prepared by in vitro transcription.…”
Section: Rna Bind-n-seq Protein Purification and Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation